EVALUASI PERAN CAMAT DALAM PELAKSANAAN PROGRAM SATU MILYAR SATU KECAMATAN (SAMISAKE) TAHUN 2014-2015 DI KECAMATAN SIULAK MUKAI KABUPATEN KERINCI - Yoddizal Ali; Otong Rosadi (UNES Journal of Swara Justisia, 2017)
The State of Indonesia emphasizes the principle of social justice explicitly. Article 27 paragraph (2), Article 28H paragraph (3) and 34 paragraphs (1), (2), (3) and paragraph 4) of the 1945 Constitution of the Republic of Indonesia mandate government responsibility in the development of social welfare. The Central Government provides regional autonomy to improve the welfare of the people within the framework of the Unitary State of the Republic of Indonesia. Local Government shall be given the right and authority to arrange and manage their own community welfare based on Law Number 12 Year 2009 regarding Social Welfare. One Billion One District Program is one of the Jambi Provincial Government's programs for the social welfare development of rural communities. This program was implemented by delegating some tasks and authority of the Governor of Jambi to the regent as head of the district administration. This research was conducted in Siulak Mukai Subdistrict with interview technique to get research data. In Siulak Mukai sub-district the success of this program in 2014-2015 is inseparable from the role of the sub-district head through the activities of home surgery, the cost of education of poor students / students, the procurement of agricultural machinery and non-agricultural equipment for farmer groups, business capital assistance, labor training and Health Insurance Area. However, in the implementation of this Samisake program there are several obstacles experienced by the subdistrict head, such as incomplete document of program beneficiary and limited operational fund.